Integrated physiologic, proteomic, and metabolomic analyses of Malus halliana adaptation to saline–alkali stress. Issue 1 (1st August 2019) - Jia, Xu-mei; Zhu, Yan-fang; Hu, Ya; Zhang, Rui; Cheng, Li; Zhu, Zu-lei; Zhao, Tong; Zhang, Xiayi; Wang, Yan-xiu
Abstract: Saline–alkali stress is a severely adverse abiotic stress limiting plant growth. Malus halliana Koehne is an apple rootstock that is tolerant to saline–alkali stress. To understand the molecular mechanisms underlying the tolerance of M. halliana to saline–alkali stress, an integrated metabolomic and proteomic approach was used to analyze the plant pathways involved in the stress response of the plant and its regulatory mechanisms. A total of 179 differentially expressed proteins (DEPs) and 140 differentially expressed metabolites (DEMs) were identified. We found that two metabolite-related enzymes (PPD and PAO) were associated with senescence and involved in porphyrin and chlorophyll metabolism; six photosynthesis proteins (PSAH2, PSAK, PSBO2, PSBP1, and PSBQ2) were significantly upregulated, especially PSBO2, and could act as regulators of photosystem II (PSII) repair. Sucrose, acting as a signaling molecule, directly mediated the accumulation of D-phenylalanine, tryptophan, and alkaloid (vindoline and ecgonine) and the expression of proteins related to aspartate and glutamate (ASP3, ASN1, NIT4, and GLN1−1). These responses play a central role in maintaining osmotic balance and removing reactive oxygen species (ROS). In addition, sucrose signaling induced flavonoid biosynthesis by activating the expression of CYP75B1 to regulate the homeostasis of ROS and promoted auxin signaling by activating the expression of T31B5_170 to enhance the resistance of M. halliana to saline–alkali stress. The decrease in peroxidase superfamily protein (PER) and ALDH2C4 during lignin synthesis further triggered a plant saline–alkali response. Overall, this study provides an important starting point for improving saline–alkali tolerance in M. halliana via genetic engineering.